The air war in Ukraine : the first year of conflict - Henriksen, Dag; Bronk, Justin (2025)
"This book provides a comprehensive account of the use of airpower in the first year of the Ukraine conflict. Owing to the need to avoid direct war with Russia, NATO did not create a No-Fly Zone over Ukraine and the initial contest for air superiority ended in an uneasy state of mutual denial. Nevertheless, Russia's bombardment using long-range missiles meant that the need to provide Ukraine with effective ground-based air defense systems and fighter jets became a topic of public debate. The rationale of this book, therefore, is to provide an analysis of why all these facets of the air war over Ukraine during the first year of the conflict played out as they did. While NATO airpower doctrine prescribes the destruction of an enemy state's Integrated Air Defense System (IADS) and air force in the opening phase of a conflict to gain air superiority, and then employ decisive firepower and surveillance over the ground war, neither side has been able to achieve this. Western doctrine holds that control of the air is a vital and decisive factor in any modern war, but the war in Ukraine has largely been decided by grinding land combat. An overarching theme of the book, therefore, is to explain the Russian failure to achieve air superiority, and how this fact shaped the subsequent employment of airpower and the broader course of the first year of the war in a way that no one had predicted before the invasion. This book will be of much interest to students of air power, military and strategic studies, Russian and eastern European politics, and International Relations.